Modern methodological approaches for evaluating energy efficiency and environmental pollution: Emerging trends and technological innovation perspectives - Yiying Cao; Fouad Jamaani; Bo Qin (Energy Strategy Reviews)
This study analyzes the causal link between technological advancement, environmental degradation, energy usage, and sustainable economic development in China. The paper looks at the extent to which expansion in energy and carbon dioxide emissions can be explained using the Environmental Kuznets Curve model. Only the annual data from the WDI is considered; therefore, only the data range from 1990 to 2019 is used. This work also uses the FMOLS technique to establish the nature of the long-run causal relationship between the variables used in the analysis and establish that environmental quality has worsened in China during the period considered. The result shows that renewable and non-renewable energy sources, along with technological advancement, have a significantly positive impact on CO2 emissions, suggesting that they are detrimental to the environment. Nevertheless, the results confirm the EKC hypothesis since the coefficient estimates for GDP growth are positive, whereas those for the square of this variable are negative. The results also highlight the existence of a unidirectional causality between the Chinese GDP and carbon emissions while reporting on a bi-directional causality between economic growth and energy consumption. This research explores the impact of technological changes and energy consumption on environmental pollution in China, examining the issue left unexplored in understanding the effects of technological change and energy usage on sustainable economic growth. Although many prior studies have focused on the EKC model, very little research has specifically explored the effects of both renewable and non-renewable energy sources on China's environmental quality. This paper is, therefore, a direct attempt at filling this gap by identifying the causal effect of these factors over the 1990–2019 period.